2020
DOI: 10.32672/si.v21i1.1893
|View full text |Cite
|
Sign up to set email alerts
|

Kemampuan Penalaran Matematis Siswa Melalui Model Discovery Learning Di Sekolah Menengah Aceh

Abstract: Tujuan dari penelitian ini adalah untuk menyelidiki perkembangan kemampuan penalaran matematis siswa melalui Model Discovery Learning di SMPN 6 Banda Aceh.Penelitian ini menjalankan pendekatan kuantitatif dan kualitatif secara bersama-sama (mix method) dengan jenis penelitian Concurrent Triangulation Strategy.Populasi penelitian yaitu seluruh siswa kelas VIII-4 SMPN 6 Banda Aceh yang berjumlah 30 siswa. Sedangkan sampel penelitian yaitu lima siswa yang terdiriatas satu kelompok belajar yang dipilih secara rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Hidayati (2013); Arianto, Sulianto, & Azizah (2019); Nashihah, sulianto & Untari (2019); Izzah & Azizah (2019); Hidayatullah, Sulianto, & Azizah (2019) measure the ability of reasoning using indicators to have comprehension, think logically, understand negative examples, think deduction, think systematically, think consistently, draw conclusions, determine methods, make reasons and determine strategies. Zubainur, Jannah, Syahjuzar, & Vello (2020) Results indicated that the mathematical reasoning skills of the students are increasing through the Discovery Learning Model. The result of this research is that applying the Discovery Learning Model will improve the mathematical reasoning capabilities of the students.…”
Section: Make Reasons and Determine Strategymentioning
confidence: 97%
“…Hidayati (2013); Arianto, Sulianto, & Azizah (2019); Nashihah, sulianto & Untari (2019); Izzah & Azizah (2019); Hidayatullah, Sulianto, & Azizah (2019) measure the ability of reasoning using indicators to have comprehension, think logically, understand negative examples, think deduction, think systematically, think consistently, draw conclusions, determine methods, make reasons and determine strategies. Zubainur, Jannah, Syahjuzar, & Vello (2020) Results indicated that the mathematical reasoning skills of the students are increasing through the Discovery Learning Model. The result of this research is that applying the Discovery Learning Model will improve the mathematical reasoning capabilities of the students.…”
Section: Make Reasons and Determine Strategymentioning
confidence: 97%
“…TIMSS results also reveal that several countries have below-average mathematics scores, such as Kuwait, South Africa, and Indonesia (Mullis et al, 2016;Mandasari, 2021). For Indonesia, students' mathematical reasoning abilities is still under-performed (Fatra et al, 2022;Mejía-Rodríguez et al, 2021;Zubainur et al, 2020). This data is reinforced by the results of previous research, which indicated that the average percentage of students' mathematical reasoning abilities in the aspect of presenting mathematical models in writing and pictures, making conjectures, manipulating finding patterns, or the nature of mathematical phenomena needs improvement (Fadhillah, 2019;Priyani & Ekawati, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…The ability to think appears when students are unable to solve problems easily. The characteristics of the habits of mind include making questions to solve problems, gathering evidence and choosing the right strategy for solving the problem (Askew, 2020;Yandari et al, 2019;Zubainur et al, 2020). This trait, in fact, has an associative relationship with reasoning ability (Indriani & Imanuel, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This can be interpreted that mathematical reasoning skills need to be developed. However, there have been many research results showing that students' low mathematical reasoning was caused by the teacher only providing the subject with examples and routine problem exercises, but when given non-routine questions, students experienced difficulties when they had to start determining the solution (Fuadi et al, 2016;Indriati, 2018;Izzah & Azizah, 2019;Napitupulu et al, 2016;Nasution et al, 2019;Putri et al, 2019;Zubainur et al, 2020). Material that concentrates on non-routine problems is found in material on trigonometry.…”
Section: Introductionmentioning
confidence: 99%